PENGOLAHAN SAMPAH ORGANIK RUMAH TANGGA MENJADI PUPUK KOMPOS DI DESA PAHLAWAN SETIA KECAMATAN TARUMAJAYA KABUPATEN BEKASI - Munajat Qarnain; Putra Wisnu Agung Sucipto; Novi Laura Indrayani (Universitas Islam 45 Bekasi, 2022)
Garbage is waste from human activities or natural processes in solid form. Waste can be divided into organic waste and inorganic waste. household activities is one of the producers of the amount of organic waste. The amount of organic waste has the highest percentage compared to other types of waste. Every time people produce waste, both organic and inorganic, but not many realize it. One of the sources of waste is from community settlements or commonly called household waste. training on how to process household organic waste into fertilizer. With this socialization and training, it is hoped that the community will understand how to process household waste. The KKN-DT program carried out by the author is located in Pahlawan Setia Village, Tarumajaya District, Bekasi Regency. The implementation mechanism is by gathering community representatives to participate in the briefing. Direct assistance and training in making compost from household organic waste carried out in accordance with the directions at the time the socialization was carried out. The KKN-DT program in Pahlawan Setia Village, Bekasi Regency began with licensing the program implementation to the Local Apparatus (RT/RW). The socialization was carried out face-to-face at the house of the Deputy Head of the Setia Pahlawan Village. This socialization explains the meaning of waste, types of waste, how to sort organic and inorganic waste, the impact of waste on society, and explains how to process waste, namely Reuse, Reduce, Recycle.